Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Sektor Pertambangan Tahun 2017-2021 - Shiddiq, Mohammad; Ibam, Muhammad Sabrian Oehoedoe (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to obtain empirical evidence regarding the influence of financial ratios on stock prices. The population in this research is mining sector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sampling technique used was purposive sampling so that a total of 70 observations were obtained. The hypothesis test used is multiple linear regression analysis with a significant t test to see the significant level of influence of each variable and the direction of that influence. The research results can explain that the ROE variable has a significantly positive effect on share prices. As well as the DER variable, it has a significant negative effect on stock prices. The ROA variable has a negative influence on share prices and an insignificant effect on share prices. Meanwhile, NPM and QR have a positive influence on share prices and do not have a significant influence on share prices.